Influence of surface salinity gradient on dinoflagellate cyst community structure, abundance and morphology in the Baltic Sea, Kattegat and Skagerrak. (20th March 2015) - Sildever, Sirje; Andersen, Thorbjørn Joest; Ribeiro, Sofia; Ellegaard, Marianne
Abstract: Changes in dinoflagellate cyst forming species composition, abundance and morphology along the surface salinity gradient in the Baltic Sea, Kattegat and Skagerrak were investigated and compared with detailed surface salinity data. A strong positive correlation was found between species diversity and surface salinity ( R 2 = 0.94; n = 7) in the Baltic Sea–Kattegat–Skagerrak system. The most pronounced decrease in dinoflagellate cyst diversity occurred between Kattegat and the Arkona basin, where the surface salinity also steeply declined. Overall, the total cyst abundance decreased along the salinity gradient. However, in the Gotland and particularly in the Northern Central basin cyst concentrations were elevated compared to the surrounding basins and the cyst community was dominated by heterotrophic cyst-producing dinoflagellate species. Possible factors behind this observation are discussed, with increased nutrient supply as the most likely primary cause. In addition, surface salinity was also confirmed to influence process length development of Operculodinium centrocarpum ( R 2 = 0.86; n = 145), which was the most abundant species in this study. Graphical abstract: Highlights: Dinoflagellate cyst communities in the Baltic Sea were studied. Cyst forming dinoflagellate species diversity decreases with surface salinity. Average process length of Operculodinium centrocarpum is influenced by surface salinity. Changes in community structure potentially due to high nutrient concentration.